Cost of implementing a doxycycline test-and-treat strategy for onchocerciasis elimination among settled and semi-nomadic groups in Cameroon. - Guillaume Trotignon; Ruth Dixon; Kareen Atekem; Laura Senyonjo; Joseph Kamgno; Didier Biholong; Iain Jones; Rogers Nditanchou (Public Library of Science (PLoS), 2023)
Background Onchocerciasis is a neglected tropical disease with 217.5 million people globally at risk of having the infection. In both settled and semi-nomadic communities of Massangam Health District in Cameroon, Sightsavers has been carrying out test-and-treat with doxycycline and twice-yearly ivermectin distribution. This paper focuses on the cost of test-and-treat with doxycycline in the two community contexts of settled and semi-nomadic. Methods For the valuation, a combination of gross or micro-costing was used to identify cost components, as well as bottom-up and top-down approaches. The opportunity costs of vehicle and equipment use were estimated and included. Not included, however, were the opportunity costs of building use and Ministry of Public Health staff salaries. We only captured the incremental costs of implementing test-and-treat activities as part of a functional annual community-directed treatment with the ivermectin programme. Results We estimate the economic cost per person tested and cost per person treated in Massangam to be US$135 and US$667 respectively. Total implementation cost in the settled community was US$79,409, and in the semi-nomadic community US$69,957. Overall, the total economic cost of implementing the doxycycline test-and-treat strategy for onchocerciasis elimination in Massangam came to US$168,345. Financial costs represented 91% of total costs. Conclusions Unit costs of test-and-treat in both settled and semi-nomadic communities are higher than unit costs of community-directed treatment with ivermectin. However, it is critical to note that a two-year implementation shows a significantly larger reduction in infection prevalence than the preceding 20 years of annual community-directed treatment with ivermectin. Test-and-treat with doxycycline may be a cost-effective intervention in places where the prevalence of microfilaria is still high, or in hard-to-reach areas where community-directed treatment with ivermectin and MDA coverage are not high enough to stop transmission or where marginalised populations consistently miss treatment.